Reform of higher education and the return of 'heroic' leadership: The case of Denmark - Stephen Carney (Management Revue, 2007)
Denmark is experiencing a comprehensive package of educational reform aimed at enabling that country to recalibrate itself to the demands of the so-called 'global knowledge economy'. In relation to the higher education sector, a new system of university governance is being implemented where boards are appointed (ultimately) by the State and comprised of a majority of members external to the institution. To further shape (if not direct) the work of universities, the new University Law requires that institutions prepare a 'development contract' with the Ministry, and that this is used as a framework within which universities direct their activities. To facilitate this process a new conception of leadership is invoked. Whilst university leaders ('rektors' in the Danish context) were previously elected by the academic staff of the institution, the new arrangements require that they be appointed by the board which looks to the rector to 'run' the institution and fulfil the demands of the development contract on their behalf. The study reported here utilises ethnographic method to explore such issues at a time of unprecedented change in Denmark. Notions of the leader as 'hero' - common in contemporary universities despite the general shift in the business world to notions of transformational and distributed leadership - appear not only difficult to eradicate but positively emboldened by the current reform movement. The paper explores different understandings of leadership, both in the literature and 'in action' via the perspectives of university leaders and decision-makers in the Danish case, before considering whether the current reforms make necessary such models of control and if the scope of action of such leaders is seriously curtailed by contemporary education policy.
Keywords: 650; leadership; university reform; education policy